Sustainable local development in citizen and community spheres. Implications for the governance of natural resources - Carreón Guillén, Javier (2013)
The economic, political, citizen, and community spheres, whether global or local, are regulated by systems of governance, which create public interest agendas including tariffs for public services derived from the use of natural resources. In this regard, this paper presents the agreements and disagreements between entrepreneurial, municipal, citizen, and community organizations to establish local development scenarios in reference to the global market. This discussion will create a series of representations that symbolize the dissonance between prosperity and austerity in order to contrast lifestyles oriented towards globalization and livelihoods aimed at sustainability. In this context, different identities have emerged from the alliances between civil and business organizations, in which development is not necessarily a priority; however, such vicissitudes provide central themes for the discussion of economic models.  This paper is important because it envisages a governance scheme that permits including natural resources in the civil, political, and business agenda.  In other words, governance regulates the intrusion of transnational corporations in communities and the inclusion of SMEs in the international market.